Evaluasi Kebijakan Alokasi Dana Desa di Desa Tinggede Kecamatan Marawola Kabupaten Sigi - Ahmad, Saskia Khaerunisya; Muhammad Rapi; Nasir Mangasing (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
ABSTRACT Saskia Khaerunisya Ahmad B 101 20 036 with the title “Evaluation Of Village Fund Allocation Policy In Tinggede Village Marawola District Sigi Regency”. Guided by Nasir Mangngasing as the main Supervisor with Muhammad Rapi as the Supervisor. This study aims to determine the Evaluation of Village Fund Allocation Policy in Tinggede Village, Marawola District, Sigi Regency. The research method used is Descriptive Qualitative, which provides a systematic, factual or real explanation of the subject or data obtained at the place of research. The data collection techniques used are literature studies, observations and interviews with informants in depth and documentation to collect the data needed in the form of secondary data and primary data. While the informants in this study amounted to 5 people, namely 3 people from the Tinggede village office, Marawola District, Sigi Regency, 1 person from the Village Consultative Board, and 1 person from the Marawola District Office. The theory used in this study is the theory of William N. Dunn where there are 6 indicators used in the Evaluation stage of Village Fund Allocation Policy in Tinggede Village, Marawola District, Sigi Regency. The six indicators are, Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Appropriteness. Based on the results of the study, it shows that the evaluation of Village Fund Allocation Policy in Tinggede Village, Marawola District, Sigi can be said to have not run well. This is caused by the aspect of effectiveness, which has not gone well enough because on the part of the Tinggede Village Government in terms of payroll has not been in accordance with the desired expectations because Tinggede village is a large village in Sigi Regency causing the village government to complain about the amount of salary given to them. From the aspect of efficiency, it has not run optimally in terms of time efficiency, namely the factor of delay in the issuance of the Regent Regulation on Village Fund Allocation. And from the aspect of adequacy, the desired results in the Village Fund Allocation budget to the satisfaction and level of needs of the Village Government are considered insufficient and satisfactory to the Tinggede Village Government. Keywords: Policy Evaluation, Village Fund Allocation, Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Appropriteness.